Recruitment and Retention of Early Childhood Educators in Ghana - Abdulai, Ahmed (Advances in Social Sciences Research Journal, 2015)
The purpose of the study was to determine factors that influences and shapes early childhood educators decision to choose early childhood education as a profession, and also to determine their level of job satisfaction and intention to stay at their jobs. As part of the aims of the study, recruitment processes prevalent at the study area with regards to early childhood education was also investigated. Purposive sampling was used where 143 early childhood educators from public and private early childhood centers volunteered to participate in the study. Using a descriptive (quantitative) research method of the survey type, questionnaires were administered to participants. In all, four research questions and two hypothesis guided the study with participants ranking love of teaching at the early childhood level and teaching in general as the most important reasons for choosing early childhood as a career, and good salary and job security been the lest of the factors influencing career choice. Also, overall responses by participants reflected job satisfaction though most participants had intentions to leave their jobs. With regards to recruitment processes, ‘word of mouth’ and ‘walk-in’ as opposed to advertisements in the media served as the most sourced channel of job advertisement.